Delia Domínguez: Words for the Mass of the Universe (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article key aspects on the poetic world of Chilean writer Delia Domínguez are discussed: transcended rurality, memoirs on German ancestors, natives and Spaniards, intercultural, feminist, peasant effects pertaining to Delia Domínguez´s poetry. Within this framework, historical and sociological references are analyzed. These references have to do with Chile´s southern farming setting where the poet was born, raised and lived up to her teenage years. All of this is crucial when analyzing Delia Domínguez´s poetics in accordance with the author of this article.
Keywords: Delia Domínguez; feminine chilean poetry; poetry of rurality; poetry and religiosity